Design and implementation of a microinverter for solar PV rooftops - Dome Sulong (2018)
© 2015 IEEE. This paper presents design and implementation of a microinverter for solar PV rooftops. The proposed microinverter consists of a flyback inverter and a dc active filter that can operate independently in parallel. The flyback inverter, controlled in digital peak current mode, regulates the full-wave rectified sinusoidal current, later which is alternately inverted and injected into the grid. The dc active filter regulates the smooth current/power drawn from a PV module by using cascaded PI controllers. The proposed topology has several advantages: 1) eliminating a bulky electrolytic capacitor at the input filter stage, 2) using a long lifetime and reliable film capacitor, 3) efficiently handling flyback transformer leakage energy. The design and control of the proposed topology are presented and discussed in detail. A 100W/220V/50Hz prototype is developed and tested. The experimental results show that the microinverter is capable of regulating the sinusoidal current fed into the grid, actively filtering the dc current/power and achieving reasonably high energy conversion efficiency.